Search 72,378 tutors FIND TUTORS
Search for tutors
Ask a question
0 0

how to do (6-c)+3(2c-7)=1

Tutors, please sign in to answer this question.

1 Answer

Let's work an example like yours that will require similar steps to complete.

Say we need to solve the following equation for 'b':

(5-b) + 4(3b - 1) = 23.

The first step would be to expand the LHS by distributing the 4.

5 - b + 12b - 4 = 23.

Now simplify this as follows, remembering we can reorder the terms if it helps to make it more clear.

12b - b + 5 - 4 = 23

11b + 1 = 23.

Subtract 1 from both sides to begin isolating 'b'.

11b = 22.

Finally, divide both sides by 11.

b = 2.

You would do well to check that this indeed is a correct solution to the original equation.

If you followed that example, I would suggest you try your problem again, as it is very similar to this example.

Hope that helps.